Social and emotional aging.[article]. - Charles, Susan T.; Carstensen, Laura L.
The past several decades have witnessed unidimentional decline models of aging give way to life-span developmental models that consider how specific processes and strategies facilitate adaptive aging. In part, this shift was provoked by the stark contrast between findings that clearly demonstrate decreased biological, physiological and cognitive capacity and those suggesting that people are generally satisfied in old age and experience relatively high levels of emotional well-being.In recent years, this supposed "paradox" of aging has been reconciled through careful theoretical analysis and empirical investigation. Viewing aging as adaptation sheds light on resilience, well-being, and emotional distress across adulthood.
Keywords: Emotion regulation; Aging; Well-being.; Affective well-being.